Regional Trends in the Development of Mechanical Engineering in Ukraine: A Statistical Assessment - Ishchuk, S. O. (Statistics of Ukraine, 2021)
The performance in mechanical engineering is determined by the innovation capacity of the industry and the overall socio-economic development of a country: in industrially developed countries, like Germany or Japan, its contribution to the gross domestic product (GDP) amounts to 50%. The mechanical engineering in Ukraine lags behind the majority of EU countries by its economic contribution, and its segment in the GDP measured in absolute figures is comparable with its analogue in a small country like Slovenia. The article’s objective is to determine key tendencies in the mechanical engineering development in Ukraine on the basis of a statistical assessment of the operational trends in mechanical engineering companies in the regional dimension. Results of the author’s studies enabled to determine the dynamics and peculiarities of production and foreign economic activities in mechanical engineering companies in Ukraine in the regional dimension. It is demonstrated analytically that the mechanical engineering is concentrated mainly in the Eastern regions of Ukraine (Dnipropetrovsk, Donetsk, Zaporizhzhia, and Kharkiv regions), which cumulative share in the overall output of this industry was 46.34% in 2020, against 53.81% in 2010. The structural change revealed by the author showed that a growth in the industry’s output and exports had occurred mainly in the regions hosting transnational corporations operated by tolling schemes (Vinnytsia, Volyn, Transcarpathia, Zhytomyr, Ivano-Frankivsk, Lviv, Ternopil, Khmelnytsk, and Chernivtsi regions). The author’s grouping of regions by type of specialization of the mechanical engineering is made. It was demonstrated that the overwhelming majority of the regions ((11 in 2019 against 9 in 2014) were specialized on the manufacturing of automobile vehicles, trailers and semitrailers and other transport vehicles. The key tendencies specific for the mechanical engineering in Ukraine in 2010–2020, which are mainly adverse ones, were substantiated: production recession; the worsening technological structure of the industry’s output; the growing dependence of the domestic companies on imports, give-and-take materials in particular; the increasing prevalence of imports over exports; the worsening structure of exports. The main challenges and threats to the development of mechanical engineering in Ukraine in the globalization context are outlined.